Normal and reverse flow injectionâspectrophotometric determination of thiamine hydrochloride in pharmaceutical preparations using diazotized metoclopramide - Mouayed Q. Al Abachi; Hind Hadi (Elsevier, 2012)
Simple and sensitive normal and reverse flow injection methods for spectrophotometric determination of thiamine hydrochloride (THC) at the microgram level were proposed and optimized. Both methods are based on the reaction between THC and diazotized metoclopramide in alkaline medium. Beerâs law was obeyed over the range of 10â300 and 2â90Â Î¼g/mL, the limits of detection were 2.118 and 0.839Â Î¼g/mL and the sampling rates were 80 and 95 injections per hour for normal and reverse flow injection methods respectively. The application of both methods to commercially available pharmaceuticals produced acceptable results. The flow system is suitable for application in quality control processes. Keywords: Thiamine, Metoclopramide, Flow injection, Spectrophotometry